The effect of vitamin K insufficiency on histological and structural properties of knee joints in aging mice. Issue 3 (September 2020) - Shea, M. Kyla; Booth, Sarah L.; Harshman, Stephanie G.; Smith, Donald; Carlson, Cathy S.; Harper, Lindsey; Armstrong, Alexandra R.; Fang, Min; Cancela, M. Leonor; Márcio Simão,; Loeser, Richard F.
Summary: Objective: While a role for vitamin K in maintaining joint tissue homeostasis has been proposed based on the presence of vitamin K dependent proteins in cartilage and bone, it is not clear if low vitamin K intake is causally linked to joint tissue degeneration. To address this gap, we manipulated vitamin K status in aging mice to test its effect on age-related changes in articular cartilage and sub-chondral bone. Methods: Eleven-month old male C57BL6 mice were randomly assigned to a low vitamin K diet containing 120 mcg phylloquinone/kg diet (n = 32) or a control diet containing 1.5 mg phylloquinone/kg diet (n = 30) for 6 months. Knees were evaluated histologically using Safranin O and H&E staining, as well as using micro-CT. Results: Eleven mice in the low vitamin K diet group and three mice in the control group died within the first 100 days of the experiment (p = 0.024). Mice fed the low vitamin K diet had higher Safranin-O scores, indicative of more proteoglycan loss, compared to mice fed the control diet (p ≤ 0.026). The articular cartilage structure scores did not differ between the two groups (p ≥ 0.190). The sub-chondral bone parameters measured using micro CT also did not differ between the two groups (all p ≥ 0.174). Conclusion: Our findings suggest low vitamin K status can promote joint tissue proteoglycan loss in older male mice. Future studies are needed to confirm our findings and obtain a better understanding of the molecular mechanisms underlying the role of vitamin K in joint tissue homeostasis.